Tribological Behavior of Polytetrafluoroethylene Coatings Based on LY12 Substrates in the Space Environment - 袁兴栋 刘勇 杨德庄 何世禹 (Shanghai jiao tong da xue xue bao, 2014)
The spacecraft space radiation environment was simulated by 60Co source. The polytetrafluoroethylene （PTFE） coatings were fabricated on LY12 substrates. And the effect of gamma （7） irradiation on the tribological behavior of PTFE coatings under vacuum conditions was investigated. Results indicate that the radiation dose has insignificant effect on the friction coefficient of PTFE coatings, and the wear of PTFE coatings reduces with the increase of gamma dose. As the gamma dose was 100 kGy, the friction coefficient of the PTFE coatings first increased with the increase of sliding velocity and then decreased, and the wear of the PTFE coatings decreased with the increase of sliding speed. As the gamma dose was 100 kGy, the friction coefficient of the PTFE coatings first decreased with the increase of load and then increased, and the wear rate of PTFE coatings increased with the increase of load. Scanning electron microscoDe was utilized.